2008
DOI: 10.1161/circresaha.108.173740
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Age, and Regional Differences in L-Type Calcium Current Are Important Determinants of Arrhythmia Phenotype in Rabbit Hearts With Drug-Induced Long QT Type 2

Abstract: Abstract-In congenital and acquired long QT type 2, women are more vulnerable than men to Torsade de Pointes. In prepubertal rabbits (and children), the arrhythmia phenotype is reversed; however, females still have longer action potential durations than males. Thus, sex differences in K ϩ channels and action potential durations alone cannot account for sex-dependent arrhythmia phenotypes. The L-type calcium current (I Ca,L ) is another determinant of action potential duration, Ca 2ϩ overload, early afterdepola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 57 publications
11
122
0
7
Order By: Relevance
“…We previously reported that female rabbit hearts express higher protein levels of Cav1.2␣ and NCX1 and have significantly higher current densities of I Ca,L and I NCX (25-30%) at the base compared with the apex. The greater Ca 2ϩ influx via I Ca,L and reverse mode I NCX lead to greater SR Ca 2ϩ overload and a greater propensity to EADs in female myocytes isolated from the base compared with those isolated from the apex, endocardium or isolated from male hearts (17,52,65).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that female rabbit hearts express higher protein levels of Cav1.2␣ and NCX1 and have significantly higher current densities of I Ca,L and I NCX (25-30%) at the base compared with the apex. The greater Ca 2ϩ influx via I Ca,L and reverse mode I NCX lead to greater SR Ca 2ϩ overload and a greater propensity to EADs in female myocytes isolated from the base compared with those isolated from the apex, endocardium or isolated from male hearts (17,52,65).…”
Section: Discussionmentioning
confidence: 99%
“…37,38 L-type calcium current density has also been found to be an important predictor of arrhythmia susceptibility, likely related to its effects on intracellular calcium overload and early afterdepolarizations. 39 Spatial heterogeneity or dispersion of repolarization across the ventricular wall (transmural dispersion of repolarization) is among the strongest preclinical predictors of the potential of a drug to cause TdP. 38 This heterogeneity of repolarization relates to the differing properties of the epicardial, midmyocardial (M cells), and endocardial cells and to the heightened susceptibility of M cells to the action potential-prolonging effects of drugs that selectively block I Kr ( Figure 3).…”
Section: Drug-induced Qtc Prolongationmentioning
confidence: 99%
“…EADs are depolarisations of the membrane potential that occur predominantly during phase 2 or 3 of the cardiac action potential and can degenerate to polymorphic ventricular tachycardia [54,55]. Generation of EADs requires an inward current that is large enough to increase total inward membrane current.…”
Section: Role Of the L-type Ca 2+ Current In Induction Of Arrhythmiasmentioning
confidence: 99%